BIVARIATE MAPPING BASED ON STUDENTS SPATIAL PREFERENCES IN THE SELECTION OF STUDENTS DORMITORY IN BANDAR LAMPUNG CITY - Rachmawati Fitri Oktaviani; Mochamad Firman Ghazali; Armijon Armijon (Journal of Engineering and Scientific Research, 2023)
Boarding houses or better known as boarding houses are one of the choices of residence for overseas students from outside the island or outside the city who are studying at a university. Most students who choose a boarding house as a place to live, consider cost savings and flexible rental times. The need for boarding houses is very necessary for students. The purpose of this study is to determine the strategic location of the boarding house to be inhabited based on its main preferences. In this study, the data collection technique was in the form of distributing questionnaires, in which the distribution of this questionnaire was allowed to fill in unila students. And this research uses Geoda to generate LISA maps and uses Qgis to generate bivariate maps. The results of this study are that Kampung Baru and Kampung Baru Raya are the places where most students choose boarding houses based on the distance factor and also the rental price factor for boarding houses per year. There are 25 students who choose the location of the boarding house with the campus and the price is relatively cheaper